Pre-disaster Training for Firefighters Using Augmented Reality: Hologram Characteristics - Polikarpus, Stella; Kasepalu, Reet; Reitel, Kärt (Proceedings of the International ISCRAM Conference, 2024)
The utilization of Augmented Reality (AR) holograms in firefighters' training presents a significant opportunity for the acquisition of first responders' practical skills. Nevertheless, given that AR represents a nascent and evolving technological paradigm, its integration within the framework of the crisis management cycle has not yet been firmly established. We analysed three hologram characteristics: dimension, scalability, and interactivity and report on the results of using five holograms (one 2D and four 3D) in a training application FightARs. The holograms were tested among in-service firefighters and commanders with the purpose of improving their knowledge in pre-disaster traffic accident training involving hazardous materials. The results indicate that QR-code scanning to open non-interactive non-scalable holograms can be used effectively to integrate holograms into physical training environments. A full-scale holographic scene is useful for training situation awareness. We propose that 3D non-interactive scalable or non-scalable holograms should be used to exercise practical skills. The paper emphasizes the necessity of extensively testing and incorporating AR into the training of first responders prior to its application in the response phase of crisis management.